Two unique star-like [MnIVMnIII2LnIII] clusters: magnetic relaxation phenomena. Issue 51 (9th May 2016) - Tziotzi, Thomais G.; Siczek, Milosz; Lis, Tadeusz; Inglis, Ross; Milios, Constantinos J.
Abstract : Synthesis and magnetic properties of two tetrametallic star-like [Mn IV Mn III 2 Ln] (Ln: Gd, Dy) clusters. Abstract : Employment of H3 L 2 (=2-(β-naphthalideneamino)-2-hydroxyethyl-1-propanol) in manganese–lanthanide cluster chemistry has led to the isolation of two new isostructural tetrametallic [MnIII2Mn IV Ln III ] complexes (Ln = Gd, Dy), with the Dy analogue displaying temperature and frequency dependent out-of-phase signals, thus indicating possible single molecule magnetism behaviour.